Strategies developed by children to cope with punishment: A dialogue between psychology and social networks theory (2009)
The main objective of this exploratory descriptive research was to identify the strategies developed by children between 7 and 12 years old from southwest Bogotá to cope with punishment and to adapt themselves to their sociocultural and home environments. Anthropological methods have been used in this research because even though Psychology allows for a general conceptualization of this issue, Anthropology provides different tools for the understanding of the cultural and social elements in which the child lives. This research is composed by two different parts, in the first one children strategies to cope punishment are identified through semi-structured interviews. In the second part, through life histories, the social and cultural system of four children is described. Thus, results and discussion are separated according to this two moments, in order to try to present a dialogue between psychology and socials networks theory.